Developing an Integrated Modeling Tool for River Water Quality Index Assessment. (1st March 2017) - Lai, Y.C.; Chien, C.C.; Yang, Z.H.; Surampalli, Rao Y.; Kao, C.M.
ABSTRACT: : The goal of this study was to establish a modeling tool for river water quality with a direct linkage to the water quality index (WQI5 ) calculation and the river water quality model, the Water Quality Analysis Simulation Program (WASP), for pollutant transport modeling. The integrated WASP and WQI5 tool was field‐tested to assess pollutant loadings and their impacts on river environment. Suspended solid (SS) and electric conductivity (EC) correlation equations and the WQI5 calculation tool were included in the water quality model and direct WQI5 calculation. The SS concentration, which was influenced by river flows, had crucial effects on river water quality and WQI5 values. EC value was controlled by dissolution of soil minerals, which was affected by the watershed drainage area and surface runoff. The integrated system could establish a direct correlation for river water quality, river flow, and WQI5 .